Effect of laser corticotomy on canine retraction rate: a split-mouth randomized clinical trial - Mohammad Hossein Toodehzaeim; Fahimeh Rashidi Maybodi; Elaheh Rafiei; Pedram Toodehzaeim; Negin Karimi (BMC, 2024)
Abstract Background This study assessed the effect of corticotomy with Er: YAG (erbium-doped yttrium aluminium garnet) laser on the rate of canine retraction. Methods This randomized split-mouth controlled clinical trial was conducted on 12 patients undergoing orthodontic treatment with extraction of maxillary first premolars. Following initial leveling and alignment, an alginate impression was made from the maxillary arch, and Er: YAG laser corticotomy was performed in one of the maxillary quadrants of each patient. Canine retraction was started immediately after corticotomy by placement of nickel-titanium (NiTi) closed coil springs at both sides. At the end of each month, alginate records were repeated for 4 months. Study models were scanned, and the anteroposterior movement of canine was quantified bilaterally. Pain was also measured by a visual analog scale (VAS). Probing depth (PPD) of canines and two adjacent teeth was also evaluated and pulp vitality was assessed by performing the cold test. Data were analyzed by paired and independent t-test and one-way ANOVA (alpha = 0.05). Results The rate of canine retraction was significantly greater in the laser-assisted corticotomy quadrant than the control (P < 0.05). No significant difference existed in posterior anchorage loss, canine rotation angle, PPD, pulp vitality, or pain score between two groups (P > 0.05). Conclusions Flapless Er: YAG laser corticotomy significantly enhanced canine retraction rate with no adverse effect on other parameters.